Testing of Streptococcus pneumoniae for resistance to penicillin. - Marshall, K J (1993)
The increasing prevalence of penicillin-resistant Streptococcus pneumoniae requires antibiotic susceptibility tests that can be done with greater ease and reliability. We measured the MIC of penicillin for pneumococci by the tube macrodilution method with Mueller-Hinton broth (MHB), Haemophilus Test Medium (HTM), Todd-Hewitt broth with 0.5% yeast extract (THY), and MHB with 3% lysed horse blood (LHB). Eight (19%) and 6 (14%) of 42 pneumococcal isolates failed to generate turbid growth in MHB and HTM, respectively, whereas all pneumococcal isolates did so in THY and LHB. For those strains that replicated to turbidity, the mean MICs of penicillin were lower in MHB and HTM than in THY and LHB, with differences being significant (P < 0.05) for comparisons with LHB. Four isolates appeared to be penicillin susceptible in HTM but were actually moderately resistant in THY and LHB, and two isolates appeared to be moderately resistant but were resistant. A similar failure to detect resistance was seen with MHB. S. pneumoniae ATCC 49619, a moderately penicillin-resistant strain that has been proposed for quality control testing, gave variable results in MHB or THM and appeared to be susceptible to penicillin in some assays, whereas the MICs for S. pneumoniae ATCC 49619 in THY or LHB fell within a twofold dilution range, with geometric means of 0.16 and 0.18 micrograms/ml, respectively. Pneumococcal isolates thus may appear falsely susceptible to penicillin when tested in MHB or HTM. LHB remains the standard medium; however, because THY is an easily prepared clear medium that can be used in automated systems and appears to yield results similar to those obtained with LHB, THY deserves consideration for routine use.